Semi-analytical study on the generic degeneracy for galaxy clustering measurements - Guarnizo, Alejandro; Amendola, Luca; Vollmer, Adrian (Arxiv, 2014)
From the galaxy power spectrum in redshift space, we derive semi-analytical results on the generic degeneracy of galaxy clustering measurements. Defining the observables $\bar{A}= Gbσ_8$ and $\bar{R} = Gfσ_8$, (being $G$ the growth function,